Zambrano avec Lacan - Pedro Cordoba (Cahiers de Civilisation Espagnole Contemporaine)
Why did María Zambrano see in her sister Araceli a figure of Antigone? I propose a Lacanian reading of a text marked by the traumas of the epoch, as if the insanity of history itself had to clarify the madness of men.